From task to intervention: rethinking mental health observation practice in Scotland. (2nd February 2019) - Gillespie, Mark; McEwan, Samantha
Abstract : Deaths by suicide during enhanced (constant or special) observation practice, while relatively rare, still unfortunately occur. There have been some high profile cases of inpatient suicides within mental health settings in Scotland, which has resulted in the successful prosecution of NHS boards. Despite the increasing complexity of illness experienced by mental health inpatients, observation practice continues to be the main intervention for suicidal inpatients. Studies suggest that observation practice has not evolved with contemporary mental health practice to incorporate the parallel emergence of therapeutic mental health interventions. This article reports on the progress and initial findings of a national quality improvement programme, commissioned by the Scottish Government, to transform the practice of observation in mental health settings and to revise the national observation practice guidance. This article describes a move away from 'observation' to a therapeutic, preventative and early intervention approach to patient deterioration, which aims to improve standards of care and individualised intervention for all patients, not solely those deemed at 'high risk'.